Non-palm Plant Volatile α-Pinene Is Detected by Antenna-Biased Expressed Odorant Receptor 6 in the Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) - Ji, Tianliang; Xu, Zhi; Jia, Qingchen; Wang, Guirong; Hou, Youming (Frontiers in Physiology, 2021)
The majority of insects rely on a highly complex and precise olfactory system to detect various volatile organic compounds released by host and non-host plants in environments. The odorant receptors (ORs) are considered to play an important role in odor recognition and the molecular basis of ORs, particularly in coleopterans they are relatively poorly understood. The red palm weevil (RPW), Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae), is one of the most destructive pests of the global palm industry. Although feeding and egg oviposition behaviors of RPW can be repelled by some non-palm plant volatiles, such as α-pinene, geraniol, or 1-octen-3-ol, there is limited understanding of how RPW recognizes the non-host plant volatiles. In this study, three candidate RferOrs were identified from the Rfer-specific clade, and the tissue expression analysis used was mainly expressed in the antennae of both sexes. Functional characterization of RferOr6, RferOr40, and RferOr87 was analyzed by using the Xenopus oocyte expression system, and the results indicated that RferOr6/RferOrco was narrowly tuned to α-pinene. The behavioral experiment showed that α-pinene at the concentrations of 10 and 100 μg/μl can cause a significantly repelled behavioral response of RPW. In conclusion, this study reveals that RferOr6 is an antenna-biased expressed OR used by RPW to detect the volatile compound α-pinene in non-palm plants, and our results provide a foundation for further in vivo functional studies of Or6 in RPW, including in vivo knockout/knockdown and feeding/ovipositing behavioral studies of RPW and further pest control.